A management approach to nursing education for preventing post-cataract surgery infections: A scoping review - I Nyoman Widiadnyana; I Ketut Swarjana; Ni Luh Dwi Indrayani; I Gede Satria Astawa (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Cataracts remain the leading cause of blindness globally, and surgery is the primary treatment. Inadequate postoperative care can lead to serious complications, including endophthalmitis. Nurse-led education is critical for prevention, and its impact can be strengthened through a management function approach. Purpose: To review nursing education strategies for preventing postoperative cataract infection from a management function perspective. Method: A scoping review was conducted following PRISMA guidelines using the PCC framework (P: nurse, C: educational management, C: postoperative cataract infection). Searches were performed in PubMed (MeSH terms) and Science Direct (standard keywords) for English-language, full-text articles published between 2014 and 2024. Narrative, integrative, scoping, and systematic reviews, as well as meta-analyses, were excluded. Results: The search retrieved 166 articles (75 PubMed, 91 Science Direct). After screening and eligibility assessment, 12 articles were included. Although none explicitly examined management functions, analysis revealed their implicit application. Educational interventions, when systematically planned, organized, implemented, and evaluated, enhanced effectiveness in preventing postoperative cataract infections. Conclusion: Incorporating a structured management function approach can improve the effectiveness of nursing education in preventing postoperative cataract infections. No studies were found that directly applied this framework in cataract postoperative care, indicating a gap for future research.